High School Students' Comprehension of Kinematics Graphs wıth Peer Instruction Approach - Gok, T; Gok, O (Jurnal Pendidikan Fisika Indonesia, 2022)
The present study investigated the effects of the peer instruction approach on high school students' kinematics graphs interpretation skills and understanding of kinematics graphs. The study was conducted with 65 high school students from two groups. The first group was the experimental group and the second group was the control group. 32 students of the experimental group were taught using the peer instruction approach while 33 students of the control group were taught using the conventional teaching method. The data of the study were collected with the Test of Understanding Graphs in Kinematics. The results of the study showed that the peer instruction approach had a more positive effect on students' kinematics graphs interpretation skills and understanding of kinematic graphs than the conventional teaching method. In addition, there was a reasonable change in students' understanding of graphs and graphical thinking processes in the experimental group The students' understanding of graphs and graphical thinking processes did not change significantly in the control group. The results of the study revealed that the peer instruction approach can be used with little effort to assess and improve high school students' academic achievement in physics classes.